Molecular characterisation of methicillin-resistant Staphylococcus aureus isolates associated with outbreaks in burn wound and neonatal ward patients at healthcare centres in Gauteng, South Africa - Ehlers, M.M. (Marthie Magdaleen) (University of Pretoria, 2024)
Dissertation (MSc (Medical Microbiology))--University of Pretoria, 2019.